Elevated plasma homocysteine levels are associated with impaired peripheral microvascular vasomotor response. (June 2020) - Toya, Takumi; Sara, Jaskanwal D.; Lerman, Ben; Ahmad, Ali; Taher, Riad; Godo, Shigeo; Corban, Michel T.; Lerman, Lilach O.; Lerman, Amir
Highlights: Homocysteine > 10 μmol/L is associated with peripheral microvascular endothelial dysfunction (PMED). Homocysteine > 10 μmol/L was associated with PMED in older, obese, or hypertensive patients. The association of homocysteine and PMED was prominent in patients with B-vitamins. Homocysteine > 10 μmol/L was associated with higher major cardiovascular events in univariate analysis. Abstract: Background: Hyperhomocysteinemia (HHcy) has been proposed as an important cardiovascular risk factor (cRF). However, little is known about the association between plasma homocysteine levels and peripheral microvascular endothelial dysfunction (PMED), which is an integrated index of vascular health. Methods: This cross-sectional and retrospective cohort study included patients who underwent non-invasive PMED assessment using reactive hyperemia peripheral arterial tonometry (RH-PAT). The association between HHcy and PMED, and its impact on MACE (all-cause mortality and atherosclerotic cardiovascular events) was investigated. Results: A total of 257 patients were enrolled (HHcy > 10.0 µmol/L, N = 51; lower levels of homocysteine [LHcy] ≤ 10 µmol/L, N = 206). Patients with HHcy were older, predominantly males, and with more comorbidities than patients with LHcy ( p < 0.05 for all). RH-PAT index was lower in patients with HHcy versus LHcy ( p = 0.01). A significant association between HHcy and PMED was observed in older (≥60 years), obese (≥30 kg/m 2 ), present/past smokers and hypertensive patients. HHcy was significantly associated with PMED even after adjusting for other cRF and B-vitamins supplementation. HHcy was associated with an increased risk of MACE with a hazard ratio of 3.65 (95% CI 1.41–9.48, p = 0.01) and an adjusted hazard ratio of 2.44 (95% CI 0.91–6.51, p = 0.08) after adjustment for age (≥60 years). Conclusion: HHcy was independently associated with PMED after adjusting for cRF and B-vitamins supplementation. Thus, the link between homocysteine and MACE could be mediated by endothelial dysfunction, and will require further clarification with future studies.